Characterization of a Reconfigurable Free-Space Optical Channel for Embedded Computer Applications with Experimental Validation Using Rapid Prototyping Technology. (14th February 2007) - Gil-Otero, Rafael; Lim, Theodore; Snowdon, John F.
Abstract : Free-space optical interconnects (FSOIs) are widely seen as a potential solution to current and future bandwidth bottlenecks for parallel processors. In this paper, an FSOI system called optical highway (OH) is proposed. The OH uses polarizing beam splitter-liquid crystal plate (PBS/LC) assemblies to perform reconfigurable beam combination functions. The properties of the OH make it suitable for embedding complex network topologies such as completed connected mesh or hypercube. This paper proposes the use of rapid prototyping technology for implementing an optomechanical system suitable for studying the reconfigurable characteristics of a free-space optical channel. Additionally, it reports how the limited contrast ratio of the optical components can affect the attenuation of the optical signal and the crosstalk caused by misdirected signals. Different techniques are also proposed in order to increase the optical modulation amplitude (OMA) of the system.